Durability of Shield Effectiveness of Copper-Coated Interlining Fabrics - Bosiljka Šaravanja; Tanja Pušić; Krešimir Malarić; Anica Hursa Šajatović (Tekstilec, 2021)
The protective shield effectiveness (SE) of copper-coated polyamide and polyester interlining fabrics at frequen¬cies of 1.8 GHz, 2.1 GHz and 2.4 GHz are presented in this study. These fabrics were treated through 10 cycles of dry and wet cleaning. After the characterization of shield effectiveness, fabrics were stored in a dark and dry place. On the basis of the SE values at all measured frequencies, it was confirmed that the copper-coated protective polyester fabric had better SE durability under storage conditions than the copper-coated polyamide fabric. Accordingly, the copper-coated polyester interlining fabric is more suitable for integration into functional clothing due to its use cycle.